1 | initial version |

Is this what you need ?

```
sage: ex2 = ex.subs_expr(sinh(x/2) == (exp(x/2)-exp(-x/2))/2)
sage: ex2.exp_simplify()
e^x - 1
```

2 | No.2 Revision |

Is this what you need ?

```
sage: ex2 = ex.subs_expr(sinh(x/2) == (exp(x/2)-exp(-x/2))/2)
sage: ex2.exp_simplify()
e^x - 1
```

or even better

```
sage: w0 = SR.wild(0)
sage: ex2 = ex.subs_expr(sinh(w0) == (exp(w0)-exp(-w0))/2)
sage: ex2.exp_simplify()
e^x - 1
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.